Bitumen binders properties – Middle-European climate requirements - Radziszewski, Piotr; Sarnowski, Michał; Król, Jan B.; Kowalski, Karol J. (International Conference “Environmental Engineering”, 2017)
The article concerns the properties of bitumens and modified binders manufactured in Poland and used in Central and Eastern Europe for road paving. The aim of the article is to evaluate the properties of bituminous binders in terms of the climatic conditions of Central and Eastern Europe, taking the Polish climate as an example. In order to obtain a qualitative assessment of binders taking into account their role in the formation of road surface and its operating conditions in a wide range of temperatures, extensive research of the binders most commonly used in the construction of asphalt pavement were carried out. Aside from the results of standard tests, this article also presents the results of studies determining the functional properties of binders according to the SUPERPAVE method. Based on the results, it was found that the bituminous binders meet the requirements specified in European standards and technical guidelines. The temperature range of viscoelasticity of all the tested bituminous binders is very wide and exceeds 80 °C. However, in view of the Polish climate, an unfavourable phenomenon is a shift in the temperature range of viscoelasticity towards higher operating temperatures, at the same time lowering the binder performance at low temperatures.
Keywords: bituminous binders; climatic conditions; functional properties